2013
DOI: 10.1039/c3cp53351d
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen peroxide produced by glucose oxidase affects the performance of laccase cathodes in glucose/oxygen fuel cells: FAD-dependent glucose dehydrogenase as a replacement

Abstract: Hydrogen peroxide production by glucose oxidase (GOx) and its negative effect on laccase performance have been studied. Simultaneously, FAD-dependent glucose dehydrogenase (FAD-GDH), an O2-insensitive enzyme, has been evaluated as a substitute. Experiments focused on determining the effect of the side reaction of GOx between its natural electron acceptor O2 (consumed) and hydrogen peroxide (produced) in the electrolyte. Firstly, oxygen consumption was investigated by both GOx and FAD-GDH in the presence of sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
89
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 101 publications
(92 citation statements)
references
References 43 publications
3
89
0
Order By: Relevance
“…20 Most reported bioelectrodes employing ChOx are based on the electro-oxidation or electro-reduction of H 2 O 2 , which has been shown to act as an inhibitor to commonly-used O 2 -reducing cathodic enzymes (laccase and bilirubin oxidase). 12 Thereby, the production of H 2 O 2 can affect the performance and stability of EFCs. It is also important to note that biosensors using ChOx to quantify cholesterol as a function of H 2 O 2 are dependent on and limited by the availability of O 2 , which can affect the reproducibility of sample analysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…20 Most reported bioelectrodes employing ChOx are based on the electro-oxidation or electro-reduction of H 2 O 2 , which has been shown to act as an inhibitor to commonly-used O 2 -reducing cathodic enzymes (laccase and bilirubin oxidase). 12 Thereby, the production of H 2 O 2 can affect the performance and stability of EFCs. It is also important to note that biosensors using ChOx to quantify cholesterol as a function of H 2 O 2 are dependent on and limited by the availability of O 2 , which can affect the reproducibility of sample analysis.…”
mentioning
confidence: 99%
“…5,[9][10][11] Metalloenzymes, such as laccases, bilirubin oxidase and peroxidase, are generally used at the cathode of EFCs allowing the bioelectrocatalytic reduction of O 2 or peroxides to H 2 O. [12][13][14][15] In addition to carbohydrates, other types of enzyme substrates have been reported as fuels such as alkanes, carboxylic acids, and other organic molecules. 1,16,17 Cholesterol, a sterol lipid, is a potential fuel for EFCs that can be oxidized to cholest-4-ene-3-one by some oxidases and dehydrogenases.…”
mentioning
confidence: 99%
“…AcMWCNTs have been shown to act as an efficient docking moiety for DET between laccase and an electrode. 4,[11][12][13][14] The onset potential for the direct bioelectrocatalytic reduction of O 2 to H 2 O by laccase was found to begin at approximately +670 mV (vs. SCE) at pH 4.5. In contrast, the onset potential for the mediated bioelectrocatalytic reduction of O 2 to H 2 O by laccase via MET was found to begin at approximately +640 mV (vs. SCE) at pH 4.5.…”
Section: Resultsmentioning
confidence: 99%
“…While it appears evident that H 2 O 2 can significantly affect the catalytic/bioelectrocatalytic performance of laccase, the mechanism by which H 2 O 2 inhibits laccase remains unclear; a single study investigating the inhibition of laccase by F − previously proposed that H 2 O 2 binds to the T2 Cu of laccase. 22 Although the authors have previously demonstrated the reversible inhibition of laccase by H 2 O 2 on DET-type bioelectrodes (incorporating anthracene-modified multi-walled carbon nanotubes (AcMWCNTs)), 12,13 an inhibition mechanism for the reversible inhibition of laccase (by H 2 O 2 ) does not currently exist. Thus, this study investigates and reports the reversible inhibition mechanism by which H 2 O 2 inhibits laccase, in both an MET and DET context.…”
mentioning
confidence: 99%
See 1 more Smart Citation